TPP1 Enhances the Therapeutic Effects of Transplanted Aged Mesenchymal Stem Cells in Infarcted Hearts via the MRE11/AKT Pathway - Yu, Kaixiang; Zeng, Zhiru; Cheng, Si; Hu, Wangxing; Gao, Chenyang; Liu, Feng; Chen, Jinyong; Qian, Yi; Xu, Dilin; Zhao, Jing; Liu, Xianbao; Wang, Jian’an (Frontiers in Cell and Developmental Biology, 2020)
Background: Poor cell survival after transplantation restricts the therapeutic potential of mesenchymal stem cell (MSC) transplantation into infarcted hearts, particularly in older individuals. TPP1, a component of the shelterin complex that is involved in telomere protection, is highly expressed in young MSCs but declines in aged ones. Here, we explore whether TPP1 overexpression in aged mouse MSCs improves cell viability in vivo and in vitro. Methods: Aged mouse MSCs overexpressing TPP1 were injected into the peri-infarct area of the mouse heart after left anterior descending coronary artery ligation. In parallel, to evaluate cellular-level effects, H2O2 was applied to MSCs in vitro to mimic the microenvironment of myocardial injury. Results: In vivo, the transplantation of aged MSCs overexpressing TPP1 resulted in improved cell survival, enhanced cardiac function, and reduced fibrosis compared to unmodified aged MSCs. In vitro, TPP1 overexpression protected aged MSCs from H2O2-induced apoptosis and enhanced DNA double-strand break (DSB) repair. In addition, the phosphorylation of AKT and the key DSB repair protein MRE11 were both significantly upregulated in aged MSCs that overexpressed TPP1. Conclusions: Our results reveal that TPP1 can enhance DNA repair through the AKT/MRE11 pathway, thereby improving the therapeutic effects of aged MSC transplantation and offering significant potential for the clinical application of autologous transplantation in aged patients.